Hybridity as a process of technology's 'translation': Customizing a national Electronic Patient Record. (January 2015) - Petrakaki, Dimitra; Klecun, Ela
Abstract: This paper explores how national Electronic Patient Record (EPR) systems are customized in local settings and, in particular, how the context of their origin plays out with the context of their use. It shows how representations of healthcare organizations and of local clinical practice are built into EPR systems within a complex context whereby different stakeholder groups negotiate to produce an EPR package that aims to meet both local and generic needs. The paper draws from research into the implementation of the National Care Record Service, a part of the National Programme for Information Technology (NPfIT), in the English National Health Service (NHS). The paper makes two arguments. First, customization of national EPR is a distributed process that involves cycles of 'translation', which span across geographical, cultural and professional boundaries. Second, 'translation' is an inherently political process during which hybrid technology gets consolidated. The paper concludes, that hybrid technology opens up possibilities for standardization of healthcare. Highlights: Customization of national EPR systems involves cycles of 'translation'. Translation spans across geographical, cultural and professional boundaries. Translation is an inherently political process that consolidates hybrid EPR. Hybrid EPR opens up possibilities for standardization of healthcare.